Clinical forms of granulomatosis with polyangiitis - Marta Madej (Rheumatology, 2014)
Granulomatosis with polyangitis (GPA) is one of systemic connective tissue diseases. Necrotizing vasculitis affects small- and medium-sized vessels. Antineutrophil cytoplasmic antibodies directed against the neutrophil serine protease proteinase-3 (cANCA, PR3-ANCA) have been identified in approximately 80–95% of patients with GPA. In typical cases upper and lower respiratory tract and kidneys are involved. However GPA produce a broad spectrum of clinical symptomes, that includes: ocular and ear involvement, peripheral and central nervous system manifestations, heart and digestive tract involvement. The diffuse alveolar hemorrhage and pulmonary-renal syndrome may also occur. The diagnosis of granulomatosis with polyangiitis may cause many difficulties, specially in cases with limited organ involvement, with untypical spectrum of clinical features and in ANCA-negative patients. We attempt to present differential diagnosis of GPA in this review article.